T‐cell depleted HLA‐haploidentical HSCT in a child with neuromyelitis optica. Issue 10 (17th September 2019) - Ceglie, Giulia; Papetti, Laura; Figà Talamanca, Lorenzo; Lucarelli, Barbarella; Algeri, Mattia; Gaspari, Stefania; Li Pira, Giuseppina; Colafati, Giovanna‐Stefania; Montanari, Mauro; Valeriani, Massimiliano; Locatelli, Franco; Merli, Pietro
Abstract: Neuromyelitis optica is an immune‐mediated disease characterized by a relapsing course, resulting in progressive disability. In children, given the long life expectancy, a disease‐modifying treatment could be particularly desirable. Unfortunately, the currently available treatment strategies with this potential are scarce. Very limited data are available about the use of allogeneic hematopoietic stem cell transplantation (HSCT) for autoimmune neurological diseases. In this report, we present a pediatric case successfully treated with allogeneic HSCT from an HLA‐haploidentical donor, after ex vivo TCR/CD19‐depletion of the graft. To the best of our knowledge, this is the first case of a pediatric patient to benefit from such a treatment.